PERBEDAAN INDEKS PERIODONTAL PADA PENDERITA JANTUNG KORONER DENGAN NON PENDERITA JANTUNG KORONER DI RSUP H. ADAM MALIK MEDAN - Tengku Chairun Mamnun (Fakultas Kedokteran Gigi Universitas Sumatera Utara, 2013)
Abstract There have been studies in the last decade reported the relationship between periodontal disease and coronary heart disease (CHD). Results showed that periodontitis causes systemic inflammation which increase the risk of CHD. The findings also support that an individual with periodontal infection has a greater risk to suffer CHD than an individual without it. The aim of this study is to find the difference between periodontal index on CHD patient compared to non-CHD patient in RSUP H. Adam Malik Medan. This study was done by using the observational method and cross-sectional approach. The samples consisted of 42 CHD patients from Cardiology Polyclinic and 40 non-CHD patients from Dental Polyclinic at the RSUP H. Adam Malik Medan. They were selected with the purposive sampling method. Each subject was interviewed and underwent a clinical periodontal examination on periodontal index. The secondary data was collected from the medical record. The results showed that the mean value of the periodontal index on CHD group (5,640) was higher than of non-CHD group (1,023). In conclusion, there was a significant difference in periodontal index (p < 0,05) between CHD patients and non-CHD patients, by which CHD patients are inclined to suffer periodontal disease more than non-CHD patients Key words: periodontal disease, coronary heart disease, periodontal index